The Role of Firms and Job Mobility in the Assimilation of Immigrants: Former Soviet Union Jews in Israel 1990-2019 - Jaime Arellano-Bover; Shmuel San (Institute of Labor Economics (IZA), 2023)
We study how job mobility, firms, and firm-ladder climbing can shape immigrants' labor market success. Our context is the migration of former Soviet Union Jews to Israel during the 1990s. This setting presents unique institutional features—including the lack of barriers posed by migration regulations—and rich data availability. Differential sorting across firms and differential pay-setting within firms both explain important shares of immigrant-native wage gap levels and dynamics. Immigrants are persistently more mobile than natives and faster at climbing the firm ladder. We uncover a novel, sizable job utility immigrant-native gap when incorporating non-wage amenities into the analysis.
Keywords: J31; J61; F22; 330; assimilation; firm ladder; job mobility; firms; immigrants